Contending with the Crisis of Islam and the Myth of Confrontation - Ariate Jr., Joel F. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Review of Fred Halliday's Islam and the Myth of Confrontation: Religion and Politics in the Middle East, 2nd ed., and Bernard Lewis's The Crisis of Islam: Holy War and Unholy Terror.
Keywords: Islam; Middle East; Fred Halliday; Bernard Lewis